MENINGKATKAN MINAT BELAJAR PKn PADA MATERI PERSAMAAN KEDUDUKAN WARGA NEGARA DENGAN MENERAPKAN MODEL STUDENT TEAMS-ACHIEVENT DIVISION (STAD) DI KELAS X4 SMA NEGERI 12 BANJARMASIN - Baihaki Baihaki (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2014)
Baihaki, 2013. Improving to interests in Learning Civics of material citizen status Equation Approach With Applying Student Teams Achievement Division (STAD) in Class X-4 SMAN 12 Banjarmasin. thesis, program Study of citizenship and pancasila education department of social siences education, faculty of teacher and education science, university of lambung mangkurat. Counselor (1) Acep Supriyadi (2) Dian Agus Ruchliyadi.During this learning process Civics in class X-4 SMAN 12 Banjarmasin likely not achieve results as expected. It is seen from the students who are interested in the subject PKN brackets, so that the students' learning outcomes is low.Research objectives are: (1) To determine whether the application of the model Student Teams-Achievement Division (STAD) can be improving the students' interest in civics lesson. (2) To determine the level of students' interest in learning after using Civics model of Student Teams-Achievement Division (STAD) in the Class X-4 SMAN 12 Banjarmasin. (3) To determine student learning outcomes after using model of Student Teams-Achievement Division (STAD) in class X-4 SMAN 12 Banjarmasin. Data collection techniques used are observation, documentation and test results of learning is done through several cycles, the first cycle and second cycle. The results showed (1) the percentage of students' interest towards learning Civics using STAD cooperative learning models known to the majority of students answered